Herbal medicine for the treatment of obesity-associated asthma: a comprehensive review - Das, Aparoop; Pathak, Manash Pratim; Pathak, Kalyani; Saikia, Riya; Gogoi, Urvashee (Frontiers in Pharmacology, 2023)
Obesity is fast growing as a global pandemic and is associated with numerous comorbidities like cardiovascular disease, hypertension, diabetes, gastroesophageal reflux disease, sleep disorders, nephropathy, neuropathy, as well as asthma. Studies stated that obese asthmatic subjects suffer from an increased risk of asthma, and encounter severe symptoms due to a number of pathophysiology. It is very vital to understand the copious relationship between obesity and asthma, however, a clear and pinpoint pathogenesis underlying the association between obesity and asthma is scarce. There is a plethora of obesity-asthma etiologies reported viz., increased circulating pro-inflammatory adipokines like leptin, resistin, and decreased anti-inflammatory adipokines like adiponectin, depletion of ROS controller Nrf2/HO-1 axis, NLRP3 associated macrophage polarization, hypertrophy of WAT, activation of Notch signaling pathway, and dysregulated melanocortin pathway reported, however, there is a very limited number of reports that interrelates these pathophysiologies. Due to the underlying complex pathophysiologies exaggerated by obese conditions, obese asthmatics respond poorly to anti-asthmatic drugs. The poor response towards anti-asthmatic drugs may be due to the anti-asthmatics approach only that ignores the anti-obesity target. So, aiming only at the conventional anti-asthmatic targets in obese-asthmatics may prove to be futile until and unless treatment is directed towards ameliorating obesity pathogenesis for a holistic approach towards amelioration of obesity-associated asthma. Herbal medicines for obesity as well as obesity-associated comorbidities are fast becoming safer and more effective alternatives to conventional drugs due to their multitargeted approach with fewer adverse effects. Although, herbal medicines are widely used for obesity-associated comorbidities, however, a limited number of herbal medicines have been scientifically validated and reported against obesity-associated asthma. Notable among them are quercetin, curcumin, geraniol, resveratrol, β-caryophyllene, celastrol, tomatidine to name a few. In view of this, there is a dire need for a comprehensive review that may summarize the role of bioactive phytoconstituents from different sources like plants and marine oils in terms of their therapeutic mechanisms. So, this review aims to critically discuss the therapeutic role of herbal medicine in the form of bioactive phytoconstituents against obesity-associated asthma available in the scientific literature to date.